Products purchased from family farming for school meals in the cities of Rio Grande do Sul - Daniele Ferigollo; Vanessa Ramos Kirsten; Dienifer Heckler; Oscar Agustín Torres Figueredo; Julian Perez-Cassarino; Rozane Márcia Triches
ABSTRACT OBJECTIVE This study aims to verify the adequacy profile of the cities of the State of Rio Grande do Sul, Brazil, in relation to the purchase of products of family farming by the Programa Nacional de Alimentação Escolar (PNAE - National Program of School Meals). METHODS This is a quantitative descriptive study, with secondary data analysis (public calls-to-bid). The sample consisted of approximately 10% (n = 52) of the cities in the State, establishing a representation by mesoregion and size of the population. We have assessed the percentage of food purchased from family farming, as well as the type of product, requirements of frequency, delivery points, and presence of prices in 114 notices of public calls-to-bid, in 2013. RESULTS Of the cities analyzed, 71.2% (n = 37) reached 30% of food purchased from family farming. Most public calls-to-bid demanded both products of plant (90.4%; n = 103) and animal origin (79.8%; n = 91). Regarding the degree of processing, fresh products appeared in 92.1% (n = 105) of the public calls-to-bid. In relation to the delivery of products, centralized (49.1%; n = 56) and weekly deliveries (47.4%; n = 54) were the most described. Only 60% (n = 68) of the public calls-to-bid contained the price of products. CONCLUSIONS Most of the cities analyzed have fulfilled what is determined by the legislation of the PNAE. We have found in the public calls-to-bid a wide variety of food, both of plant and animal origin, and most of it is fresh. In relation to the delivery of the products, the centralized and weekly options prevailed.